2016
DOI: 10.1016/j.amepre.2016.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Preconception Care in Publicly Funded U.S. Clinics That Provide Family Planning Services

Abstract: Introduction Federal recommendations for providing quality family planning services were published in 2014 and included preconception care (PCC). This paper aims to describe the prevalence of PCC delivery among publicly funded clinics, prior to the recommendations. Methods Prevalence of providing occasional or frequent PCC in the last 3 months and having written protocols for recommended PCC screenings were estimated in 2015 using survey data collected from a nationally representative sample of publicly fund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 12 publications
2
15
0
Order By: Relevance
“…This means that in many cases, the onus for preconception care is on healthcare practitioners who see women in their routine practice, for reasons other than pregnancy planning. Elements of preconception care can occur whenever a healthcare practitioner meets a woman of childbearing age and this would include offering support for pregnancy planning or contraception counselling, and addressing nutrition and weight management 22,24,25 …”
Section: Preconception Health: An Opportunity To Prevent Noncommunicamentioning
confidence: 99%
“…This means that in many cases, the onus for preconception care is on healthcare practitioners who see women in their routine practice, for reasons other than pregnancy planning. Elements of preconception care can occur whenever a healthcare practitioner meets a woman of childbearing age and this would include offering support for pregnancy planning or contraception counselling, and addressing nutrition and weight management 22,24,25 …”
Section: Preconception Health: An Opportunity To Prevent Noncommunicamentioning
confidence: 99%
“…Conversely, we found that recommendations for routine screening of pregnancy intentions (i.e., reproductive life plan assessment), preconception health care (for men), and screening for risk factors for infertility and adverse pregnancy outcomes (i.e., STD and body mass index screening for men) were more likely in Title X compared with non-Title Xfunded clinics. Previous studies using these data have also shown enhanced preconception care service delivery in Title X-funded clinics (Robbins et al, 2016), which was attributed to institutional support from the Office of Population Affairs to Title X grantees to promote preconception care and training in reproductive life plan assessment. Although we adjusted for some differences between the two clinic categories, the differences we found in services provided by Title X funding status may also reflect the unique needs of the clients attending each type of clinic.…”
Section: Discussionmentioning
confidence: 76%
“…Although previous analyses of these study data have examined several of the preconception care services included in our analysis (Robbins et al, 2016(Robbins et al, , 2017, we were specifically interested in identifying the full set of services that may offer opportunities to prevent infertility and/or enhance fertility in family planning settings serving persons with low incomes. In particular, we found that a high proportion of publicly funded clinics reported that they provided basic infertility services for women (66%), whereas a lower proportion reported this for men (45%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preconception care (PCC) is defined as interventions that aim to identify and, when possible, modify the biomedical, behavioral, and social risks to optimize woman’s health before pregnancy with the aim of improving pregnancy outcomes [1]; In 2014, Centers for Disease Control and Prevention (CDC) and the Office of Population Affairs published clinical recommendations, “Providing Quality Family Planning Services” (QFP), and recognized PCC as a critical component of health care for women of reproductive age [2]. …”
Section: Introductionmentioning
confidence: 99%